Perspectives of Civic Upbringing as in Non formal Education - YEHOROVA, OLEKSANDRA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
The article covers the theoretical aspects and importance of civic education in its broad sense nowadays and analyzes its role, tasks, the after-school programs, best experiences and practices of after-school education in the United States in the field of civic education and upbringing. In the article civic education in the framework of U.S. out-of-school time is substantiated as a systematic object in its substantive and procedural aspects, which aims to form national, universal human values, civic activity and competencies required in the XXI century. It has been established that civic education and upbringing has been integrated in the secondary school and out-of-school education curriculum and practice, is considered as a priority task for education at the present stage in the United States and is a perspective area for nonformal education in Ukraine and beyond.